STRATEGI PEMBERDAYAAN KELOMPOK PENGEMIS GELANDANGAN ORANG TERLANTAR (PGOT) DALAM PENGENTASAN KEMISKINAN DI DINAS SOSIAL, PEMUDA, DAN OLAHRAGA KOTA SEMARANG - Fuad, Masrul; Suwitri, Sri; Sulandari, Susi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
High number of poverty from year to year is alleged as the prominent factor of the increasing quantity of beggars and homelesses (PGOT). This kind of problem is typically take place in rapid population. Government need to put a serious concern on that condition, otherwise it will be a time bomb which can explode anytime. This situation is common and become phenomenon in big cities. It is become worse since there is no legal basis exist that give a clear rule to manage such problem.The objective of this study is to investigate the obstacles faced by Social, Youth and Sport Local Service in Semarang City (Dinas). Data is obtained by formulating the strategies of PGOT reduction that is implemented by Dinas.To identify the problems of this study, I use qualitative method particularly strategic management theory. Data analysis is carried out using SWOT matrix and Litmus Test.The result of this study prove that empowering strategy done by Dinas is ineffective and far from target. Litmus Test pointed out that strategic issue in empowering PGOT is improvement role of all stakeholders (Dinas, Public Figure, Rehabilitation Office, and Academician) to create Semarang free from PGOT. In this context, the recommendation is optimalizing Dinas’ budget to improve the quantity and quality of human resources as well as drafting regulation that regulate beggars and homelesses in the terms of social welfare improvement.